Investigation of Preferred Teaching Pedagogies of Preservice Science Teachers through Individual and Team Studies - İNALTEKİN, Tufan; KİRMAN BİLGİN, Arzu (International journal of contemporary educational research, 2022)
The purpose of this research is to examine how working individually and as a team in solving pedagogical scenarios for teaching science subjects is reflected in the teaching preferences of preservice science teachers. This interpretive case study was conducted with 69 preservice science teachers studying at a university in eastern Turkey. The data of the study were collected using the teaching pedagogy preference form. The data analysis included descriptive analysis based on four instructional pedagogies: direct instruction, direct active, guided inquiry, and open inquiry. The research results revealed that preservice teachers did not sufficiently turn to inquiry-based teaching pedagogy for solving problem scenarios in both individual and teamwork. In addition, the results indicated that preservice science teachers' professional knowledge of teaching various science subjects is largely based on traditional teaching pedagogy. Based on these results, it is recommended that science educators use problem scenarios to reveal preservice teachers' inquiry-based teaching preferences.